The First Results of Introduction of the Program “Intel® Training for the Future” - Zaytseva, Т.В. (Journal of Information Technologies in Education (ITE), 2007)
Experiment has begun with 2006 under the order of the Ministry of Education and a science of Ukraine on inclusion of the program “ Intel® Training for the future” in system of preparation of the future teachers. The faculty of computer science has already small experience and first results of introduction of the given program in system of training of students of university. Skill to use a method of projects – a parameter of high qualification of the teacher, its progressive procedure of training and progress of disciples.